A tool for signage placement recommendation in hospitals based on wayfinding metrics. Issue 7 (August 2018) - Greenroyd, Fraser L; Hayward, Rebecca; Price, Andrew; Demian, Peter; Sharma, Shrikant
Navigating a healthcare facility can prove challenging to both new and existing patients and visitors. Poor or ineffective use of signage within the facility may enhance navigational difficulties. Signage strategies within facility design tend to be produced without consideration of how people typically navigate a space. Thus, strategies that 'work on paper' may not, in reality, aid or optimize patient and visitor wayfinding. Existing strategies for determining signage placement may also prove costly in terms of time spent on manual analysis of a facility's floor space, including the potential for overlooking prime signage locations when analysing large floor plans. This paper presents a tool which aims to aid signage placement strategies by analysing facility design and routes within it, based on natural wayfinding metrics found in existing literature. The tool is designed to enable quick analysis of large designs for analysing multiple routes, highlighting areas where signage placement would aid natural wayfinding. The outputs of the tool are presented as a colour map which overlays the original 3D model design, highlighting the key areas where signage may be appropriate. An example of how the tool can be utilised to aid effective sign strategy is demonstrated on a small healthcare facility design.